2014
DOI: 10.1111/sms.12233
|View full text |Cite
|
Sign up to set email alerts
|

Do nonsteroidal anti‐inflammatory drugs affect the outcome of arthroscopic Bankart repair?

Abstract: To achieve pain control after arthroscopic shoulder surgery, nonsteroidal anti-inflammatory drugs (NSAIDs) are a complement to other analgesics. However, experimental studies have raised concerns that these drugs may have a detrimental effect on soft tissue-to-bone healing and, thus, have a negative effect on the outcome. We wanted to investigate if there are any differences in the clinical outcome after the arthroscopic Bankart procedure for patients who received NSAIDs prescription compared with those who di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 32 publications
0
19
0
Order By: Relevance
“…Ultimately, we identified 4 studies on the effects of perioperative NSAIDs on healing after sports medicine procedures in humans. 3,21,22,24…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Ultimately, we identified 4 studies on the effects of perioperative NSAIDs on healing after sports medicine procedures in humans. 3,21,22,24…”
Section: Resultsmentioning
confidence: 99%
“…Among the studies included, 4 procedures were identified: 93% (4144/4451) of patients underwent anterior cruciate ligament (ACL) reconstruction, 24 3% (120/4451) underwent rotator cuff repair, 21 3% (155/4451) underwent Bankart shoulder repair, 3 and 1% (32/4451) underwent meniscal repair. 22 The type of NSAID administered was reported in 3 of 4 studies (Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations